Genotoxic and mutagenic effects of passive smoking and urban air pollutants in buccal mucosa cells of children enrolled in public school. (13th June 2017) - Cavalcante, Deborah Navit de Carvalho; Sposito, Juliana Caroline Vivian; Crispim, Bruno do Amaral; Nascimento, André Vieira do; Grisolia, Alexeia Barufatti
Abstract: Nuclear abnormalities (micronuclei and meta-nuclear changes) have been used as biomarkers to identify cell damages. As children are more vulnerable to the adverse effects of pollution when compared to adults, assessing genetic damage caused by environmental influences is of great interest. As such, the objective was to determine metanuclear (karyolysis, pycnosis, karyorrhexis, binucleated cells, chromosome bridges and micronuclei) in cells from the oral mucosa of children associated with the school environment, gender, exposure to cigarette smoke and vehicular traffic. Analyses of nuclear abnormalities were performed in exfoliated buccal cells of children from two public schools located in Dourados – MS. The data were analyzed through Kruskal–Wallis test considering a significance level of 5% ( p < .05). The results showed that children exposed to cigarette smoke presented higher levels of nuclear abnormalities than children who were not usually exposed to this type of mutagenic and genotoxic agent, suggesting that such contaminants are related to clastogenic and aneugenic effects on DNA. Moreover, female children had higher amounts of nuclear abnormalities when compared to male children. With regards to the school environment, the study results indicated statistical differences in of term chromosomal abnormalities for schools A and B. Thus, it was possible to determine that children exposed to cigarette smoke are susceptible to further genetic damage than unexposed children, and female children may be more susceptible to genotoxic and mutagenic agents. This study contributes to the current knowledge on the mutagenic characteristics of human cells, supporting the adoption of preventive Public Health measures.